Chiral phonons and phononic birefringence in ferromagnetic metal-bulk acoustic resonator hybrids - Müller, M.; Weber, J.; Engelhardt, F.; Bittencourt, V. A.S.V.; Luschmann, T.; Cherkasskii, M.; Opel, M.; Goennenwein, S. T.B.; Viola Kusminskiy, S.; Geprägs, S.; Gross, R.; Althammer, M.; et al. (Physical Review B, 2024)
Magnomechanical devices, in which magnetic excitations couple to mechanical vibrations, have been discussed as efficient and broadband microwave signal transducers in the classical and quantum limit. We experimentally investigate the resonant magnetoelastic coupling between the ferromagnetic resonance modes in metallic Co25Fe75 thin films, featuring ultralow magnetic damping as well as sizable magnetostriction, and standing transverse elastic phonon modes in sapphire, silicon, and gadolinium gallium garnet at cryogenic temperatures. For all substrates, we observe a coherent interaction between the acoustic and magnetic modes. We identify the phonon modes as transverse shear waves propagating with slightly different velocities (Δv/v≃10-5); i.e., all investigated substrates show potential for phononic birefringence as well as phonon-mediated angular momentum transport. Our magnon-phonon hybrid systems operate in a coupling regime analogous to the Purcell enhanced damping in cavity magnonics.
CRIS-Team Scopus Importer:2024-02-02